Strategi Hukum Preventif dalam Meningkatkan Perlindungan Anak di Era Digital - Muh. Fachrur Razy Mahka; Fatri sagita; Najirah Umar; Sitti Zuhriyah; Nur Lilis Sukanda (Ikatan Ahli Informatika Indonesia, 2023)
Technology advancement is inevitable in this life. The role of parents in supervising and directing the use of children's technology is very important. The purpose of this study is to determine preventive legal strategies to improve child protection in the digital age and the role of parents in Law No. 35 of 2014 on Child Protection in the digital age. The type of research used is qualitative research. The author uses a normative-juridical and sociological approach. In this study, the key informants are parents of children in Paccinongang Village, Somba Opu District, Gowa Regency. Data collection will be carried out using four methods, namely interviews, observations, and library research. The results of this study found that there are several preventive legal strategies that can be used, including the formulation and updating of regulations and digital literacy education in schools, as well as the role of parents according to Law No. 35 of 2014 on Child Protection, which is very important in maintaining and protecting the rights of children in Indonesia. This law brings relevant basic principles that can be applied in the context of child protection in the digital world. The researcher can conclude that preventive legal strategies, such as the development and updating of relevant regulations, are important steps in identifying potential risks and threats to children in the digital age. Digital literacy education in schools is a step in preparing children to face the increasingly complex digital world. The role of parents in child protection in the digital age is also essential. They must ensure the safety of children in their use of technology, protect their privacy, and provide guidance on online ethics and good behavior.